The effect of mahjong/bridge intellectual sports on the subjective wellbeing of middle-aged and older adults: an empirical analysis from the mixed cross-section data of CHARLS in China - Xia, Qi-fei; Qin, Guo-you; Yang, Fei-long; Li, Zheng (Frontiers in Public Health, 2025)
BackgroundAs China’s population ages, intellectual sports have become a key leisure activity with a significant impact on the subjective wellbeing of middle-aged and older adult individuals. These activities promote social engagement, counteract the “empty nest” phenomenon, and offer a pathway to successful aging.MethodsThis study utilized mixed cross-sectional data from the China Health and Retirement Longitudinal Study (CHARLS), encompassing 36,934 adults aged 45 and above. The relationship between intellectual sports, such as mahjong and bridge, and subjective wellbeing was analyzed using ordinal logistic regression modeling.ResultsParticipation in mahjong and bridge was positively associated with subjective wellbeing, a finding that remained consistent across multiple regression tests. Social interaction and cognitive ability emerged as critical mediators, enhancing wellbeing through increased social engagement and cognitive stimulation. Retirement status moderated this relationship, with retired individuals showing a stronger propensity to engage in these activities, thereby boosting their wellbeing. It is noteworthy that this positive impact was more pronounced among women and rural and eastern participants.ConclusionThis study elucidates the mechanisms through which mahjong and bridge influence the subjective wellbeing of middle-aged and older adult Chinese individuals. The findings offer valuable insights for policymakers, suggesting that promoting diverse cultural and sports activities within older adult communities could foster socialization, prevent cognitive decline, and ultimately enhance wellbeing.